Бібліографія етнографічних карт території України - Падюка, Н.; Сосса, Р. (Історико-географічні дослідження в Україні, 2019)
Покажчик картографічних творів розміщення українського етносу містить етнічні карти Європи та окремих держав, у складі яких перебували українські етнічні території, карти розселення слов’янських народів, карти української етнічної території або її історичних областей. Поряд з етнічними картами до покажчика включено карти конфесійні, статистичні, мовні, діалектологічні, а також загальногеографічні, політичні та фізичні, на яких показано територію розселення українського народу та його етнічні межі. Тематичний покажчик включає 168 джерел. The index of the cartographic works of the location of the Ukrainian ethnic group contains ethnic maps of Europe and individual states, which consisted of Ukrainian ethnic territories, maps of the settlement of Slavic peoples, maps of the Ukrainian ethnic territory or its historical regions. The territory of settlement of the Ukrainian people, its ethnic boundaries are reflected in various thematic maps: ethnic (ethnographic, settlements of peoples), denominational, statistical, linguistic, dialectological. Outlines of the Ukrainian ethnic territory in the first half of the twentieth century were widely distributed on geographic, political, physical maps. The thematic index of cartographic sources includes 168 items. It was concluded by working first of all on the collections of the V. Stefanyk Lviv National Scientific Library of Ukraine. The index includes only single maps of the corresponding subject, which are stored in the funds of the National Library of Ukraine named after VI. Vernadsky, Austrian National Library. Therefore, work on the pointer will continue.